Cerebelite aguda causada por vírus epstein-barr - Teive, Hélio Afonso Ghizoni; Zavala, Jorge Augusto Acurio; Iwamoto, Fábio Massaiti; Bertucci Filho, Délcio Caran; Werneck, Lineu César (My University, 2001)
A cerebelite aguda pode ocorrer em associação a infecção pelo vírus da varicela-zoster, enterovirus, caxumba, micoplasma e outros agentes infecciosos. A cerebelite aguda é uma complicação rara da infecção pelo vírus Epstein-Barr (EBV). Relatamos o caso de uma mulher de 21 anos com história de 12 dias de evolução com náuseas, vômitos, ataxia de marcha e membros, tremor cefálico e de membros, opsoclono, mioclonias e rash cutâneo. Sorologia para EBV foi positiva. A infecção pelo EBV, com complicações neurológicas, pode não se apresentar com os sinais e sintomas clássicos da mononucleose infeciosa.

Acute cerebellitis can occur in association with varicella-zoster virus, enterovirus, mumps, mycoplasma, and other infective organisms. Acute cerebellitis is a rare complication of Epstein-Barr virus (EBV) infection. We report the case of a 21-year-old woman with a 12-day history of nausea and vomiting, gait and limbs ataxia, myoclonus, tremor of head and all four limbs, opsoclonus and cutaneous rash. Anti-EBV IgG and IgM antibodies against antiviral capsid were positive and anti-EBV against virus-associated nuclear antigen was also positive. EBV infection in association with neurological findings can occur without the classic signs and symptoms of infectious mononucleosis.
Acute cerebellitis caused by epstein-barr virus: case report
Keywords: Epstein-Barr virus; Cerebelite; Complicação neurológica